Latin America and the New Renminbi (Observatorio Económico, 2012)
The speed with which the Chinese currency is beginning to be used internationally is striking. From a zero share in 2008, invoicing denominated in renminbi (RMB) today already accounts for more than 8% of China’s total foreign trade. It is unusual for a country to internationalize its currency before opening up to capital flows. Nevertheless, as a result of successive liberalization measures, the authorities have managed to have the RMB—literally “the people’s currency”—begin to accompany not only China’s foreign trade in goods and services but also lending, foreign direct investment, and portfolio transactions. Continue reading...
Keywords: Renminbi; Chinese economy; international economics; Latin America